Analisis Efektivitas Biaya Terapi Antihipertensi Kombinasi Tetap Di Satu Rumah Sakit Jakarta Selatan - Ani Rahayu; Ahmad Fuad Afdhal; Delina Hasan; Feriadi Suwarna; Okpri Meila (Faculty of Pharmacy, Universitas Gadjah Mada)
The majority of alternative antihypertensive therapies require pharmacoeconomic studies, particularly Cost Effectiveness Analysis, which is useful in balancing patients’ expenditure by determining alternative treatments that represented the most plausible health outcomes with a more reasonable budget. The objective of this study was to compare the cost effectiveness using antihypertensive fixed dose combinations (FDC) of Valsartan-Amlodipine + Furosemide and FDC of Valsartan-HCT + Amlodipin. This research applied the descriptive analytical cross-sectional method and conducted data collection retrospectively from the medical record of hypertensive patients. Meanwhile, the medication cost breakdown was obtained from Outpatient Financial Department of a Type B Hospital in south Jakarta for the period of January - June 2018. Total sample were 74 patients, consisted of 37 patients who used FDC of Valsartan-Amlodipin + Furosemide, and 37 patients who used FDC of Valsartan-HCT + Amlodipin. The parameters of this research were direct medication cost (consisted of examination cost, laboratory cost and medicines cost), indirect medication cost (consisted accommodation cost and lost productivity cost), while the effectiveness used the MAP average (Mean Arterial Pressure). The result of this research showed that the biggest medication effectiveness to lower the blood pressure is FDC of Valsartan-Amlodipin + Furosemide, with 32 patients had the average MAP 101,29 mmHg, while the FDC of Valsartan-HCT + Amlodipin with 29 patients had the average MAP 103,59 mmHg. The cost effectiveness based on ACER value of FDC of Valsartan –HCT + Amlodipin and FDC Valsartan-HCT + Amlodipin sequentially is Rp 3.922.040/MAP and Rp 4.458.034/MAP. In conclusion, the FDC of Valsartan-Amlodipin + Furosemide was more cost-effective.